Case report: Significant benefits of tislelizumab combined with anlotinib in first-line treatment of metastatic renal pelvic urothelial carcinoma with sarcomatoid carcinoma differentiation - Zhu, Shibin; Yu, Chenhao; Wang, Chongwei; Ding, Guoqing; Cheng, Sheng (Frontiers in Oncology, 2022)
Background: Renal pelvic urothelial carcinoma with sarcomatoid carcinoma differentiation is a very dangerous malignant tumor and extremely rare in clinical practice. In general, these tumors with a dismal prognosis, and there is no standard treatment. Case presentation: In this case, an 81-year-old male patient was diagnosed with right renal pelvic carcinoma. After an open right radical nephroureterectomy, postoperative pathological examination showed infiltrating urothelial carcinoma with sarcomatoid differentiation. Overexpression of programmed death ligand-1 by immunohistochemistry. The carcinoma recurred 4.5 months after surgery. After informed, tislelizumab combined with anlotinib were used as first-line treatment. The patients showed a clinical partial response that lasted for 20 months. Conclusion: This case demonstrates the efficacy of tislelizumab combined with anlotinib in patients diagnosed with metastatic renal pelvic urothelial carcinoma with sarcomatoid carcinoma differentiation. Moreover, to our knowledge, this is the first application of this treatment.